Didactic aspects of сase-study technologу use in training skilled workers of agrarian profile - Slatvinska, O (Professional Pedagogics, 2011)
A unique feature of сase-study method is a creation of problem situation from real life. The use of сase-study method while teaching a number of subjects to students of agrarian profile vocational schools will enable to intensify cognitive interest to studies, will promote the advance of research, communicative and creative skills of future agrarians.